Investigação da prevalência de mutações e fusões de genes que codificam efetores da via mapk e sua correlação com características clinico-patológicas e perfil de expressão em carcinomas papilíferos da tiroide - Bastos, André Uchimura [UNIFESP] (2016)
Papillary thyroid carcinoma (PTC) is the most prevalent subtype among thyroid carcinomas, representing about 80% of cases. Its prevalence has increased in recent years, mainly due to the increase of papillary thyroid microcarcinomas (PTC ?10 mm, PTMC). In recent decades, it became clear that genetic changes that lead to activation of the MAPK (Mitogen-Activated Protein Kinase pathway), a signaling cascade that regulates cell proliferation, differentiation and survival, are highly prevalent in PTC. Alterations in the genes encoding proteins of this pathway represent a total of approximately 70% of cases of PTC, and include chromosomal rearrangements like RET/PTC or NTRK, and mutations in RAS and BRAF genes. In addition to these changes, new fusions involving tyrosine kinases have been described recently by The Cancer Genome Atlas (TCGA). However, in a number of cases of PTCs, a genetic event associated with pathogenesis (driver changes) is still unknown ("dark-matter"). In order to describe the genetic events associated with pathogenesis of PTC in the Brazilian population, our group investigated the prevalence of BRAF V600E mutation in a sample set of 120 PTCs. In addition to determining the prevalence of this mutation (48%; n=58), we observed the association with histological subtype, clinical and pathological features associated with a poor prognosis, and loss of expression of genes involved in iodine uptake and metabolism (NIS and TSHR). These data associated with the reported in the literature suggest that BRAF V600E is a marker of poor prognosis. In the articles that originate this thesis, we initially investigated the prevalence of RET/PTC, which is the second most frequent genetic alteration in the PTC, and we evaluated the expression of TPO, PDS and TG. Fusions involving the RET gene (RET/PTC1, RET/PTC2 and RET/PTC3) were identified in 27% (32/118) of PTCs. There was no association between RET/PTC, expression of genes associated with iodine uptake and metabolism and clinic-pathologic characteristics associated with aggressiveness. In fact, the role of RET/PTC as a prognostic marker is still controversial. Besides NIS, previously reported, in this study we demonstrate that BRAF V600E mutation is also associated with the loss of TPO expression. Additionally, we identified the mutation in codon 61 of NRAS in 9% (11/118) of PTCs. When we evaluate the genetic changes in PTMC (n=40), we found no association with clinic-pathologic characteristics associated with aggressiveness, but we found that the BRAF V600E mutation is associated with a decreased expression of NIS and TPO. When PTMCs were divided into two subgroups (<7 mm vs. ?7 mm) we observed that MCPTs ?7 mm have higher extrathyroidal extension, metastasis to lymph nodes and recurrence rates, and that the decreased expression of NIS and TPO is much more evident in this group. This is probably due to the accumulation of PTMCs with BRAFV600E in the ?7 mm subgroup. These data are similar to those found in tumors larger than 10 mm, more aggressive, which suggests that despite PTMCs being, most often, clinically indolent, the subgroup of 7-10 mm with BRAF V600E could be treated in a similar manner to conventional PTC with BRAF V600E. In the second phase of this study, we investigated the presence of ETV6-NTRK3, STRN-ALK and AGK-BRAF fusion genes, recurring events in PTCs that are able to activate the MAPK pathway. We also investigated the presence of mutations in the KRAS and HRAS genes (codons 12, 13 and 61), and only one of the samples was positive for HRAS Q61R. ETV6-NTRK3 was identified in about 5% (6/116) of PTCs. ETV6- NTRK3 was exclusively found in the follicular variant of PTC (FVPTC), leading to a prevalence of 16% (6/45) in this variant. This fact is interesting, since most of the "dark-matter" is composed of PTCs of this variant. In addition, we investigate whether such mutation would have some association with the presence of the tumor capsule. ETV6-NTRK3 was found in both variants, infiltrative and encapsulated, in 50% each. As a recently new nomenclature was suggested for encapsulated FVPTC without any invasion, called noninvasive follicular thyroid neoplasm with papillary-like nuclear characteristics (NIFTP), the relationship between ETV6-NTRK3 and NIFTP variant should be further investigated. STRN-ALK was identified in 3% (4/116) of PTC and was found in both classic and FVPTC. There was no association with clinic-pathological features associated with aggressiveness. We did not find any positive sample for AGK-BRAF in this series. This finding confirms the proposition that AGK-BRAF is a likely event associated with PTCs of pediatric patients. Finally, in this initial screening, we identified that 27% (n=30) of the samples were negative for BRAF V600E (and adjacent codons), NRAS Q61, HRAS (codons 12, 13 and 61), KRAS (codons 12, 13 and 61) RET/PTC1, RET/PTC2, RET/PTC3, ETV6-NTRK3, STRN-ALK and AGK-BRAF. Our data contribute to a better understanding of the pathogenesis of PTC and collects important data regarding the use of various alterations as prognostic markers. Along with other previously published articles, and articles that will be published in future in several other populations, we hope this information can help to establish effective guidelines for the management and treatment of patients with papillary carcinoma of the thyroid.